Research on bearing capacity of soilbagged graphite tailings and numerical simulation of along empty lanes - Zhan XU; Changbo DU; Jian GAO; Fu YI; Kailong SHI (Meitan kexue jishu)
In order to analyze the bearing characteristics and failure mechanism of soilbagged graphite tailings, and to verify the feasibility of applying flexible walls in along empty lanes. The study based on the theoretical foundation of the soilbag semi-circular boundary bearing model. The model formula is modified to consider the variation of the geotextile bag volume. The microscopic parameters of the contact between graphite tailings and geotextile fabric are determined through direct shear tests and pull-out tests using PFC2D particle flow program. Numerical tests on uniaxial compression of soilbagged graphite tailings are conducted to obtain the stress-strain curves under different factors. The theoretical calculations are compared with the numerical test results to validate the rationality of the selected numerical parameters. Furthermore, the bearing mechanism and failure modes of the soilbag stack are further studied based on the contact between particles and their movement trends. Based on the overview of the working face in a specific coal mine, the flexible wall of soilbagged graphite tailings is established using PFC2D particle flow program in four different stacking arrangements: staggered in both vertical and horizontal directions, seamless in horizontal direction, seamless in vertical direction, and staggered in vertical direction. The movement of the rigid wall is simulated to represent the subsidence of the roof in the along-airway backfilling. The bearing capacity of the flexible walls in the four different stacking arrangements is analyzed to validate the feasibility of using soilbagged graphite tailings as flexible wall. The results show that during the bearing process, the tension formed by the confinement is the main factor affecting the bearing performance of the soilbags. The initial failure of the soilbags occurs at the interface between the soilbags. After the initial failure, the overall stability of the soilbag stack is not compromised. The soilbags can continue to bear load until they fracture on their sides due to the lateral constraints. The soilbags at the initial failure location primarily experience shear failure, and when complete failure occurs, the particles at the center of the soilbag experience compression consolidation. The results of the modified soilbag semi-circular boundary bearing model are close to the numerical calculation results. Among the four different arrangements, the staggered arrangement in both vertical and horizontal directions exhibits the highest bearing capacity and the smallest settlement. It meets the displacement range of roof subsidence in the along-airway backfilling and satisfies the resistance requirements of the filling material before the soilbags experience initial failure. The modeling method and results presented in this study can serve as a reference for the application of soilbag flexible walls in the side support of along empty lanes.